Bullying or Body Shaming? Young Women in Patient Body Dysmorphic Disorder - Sumi Lestari (Faculty of Psychology, Universitas Semarang, 2019)
Abstract: The aim of this research is to describe a phenomenon of body shaming as a prediction factors of young women who are suffering from body dysmorphic disorder. This research employed qualitative method and case study approach on young women suffering from body shaming and triggering the risk of body dysmorphic disorder. The respondents of this research were 3 young women suffering from body shaming in malang Indonesia. The data were collected through interview and observation. The data were analyzed by using reduction analysis by Miles and Hubberman. The result of this research showed that the three respondents suffering from body dysmorphic disorder were caused by the existence of body shaming do that it gave big contribution towards the emergence of body dysmorphic disorder and, furthermore, the dominant factor of young women body dysmorphic disorder was due to the mokcery or humiliation in regards to their body shape or body shaming.